Determination of Major Viral and Sub Viral Pathogens Incidence in Apple Orchards in Himachal Pradesh - Kumar, Surender (Springer-Verlag, 2011)
Apple is the major commercial horticulture crop in Himachal Pradesh and other hill states of Jammu & Kashmir, Uttarakhand and some parts of Northeastern states of India. In order to gather data on health status and incidence of virus and virus-like pathogens in apple orchards, survey was conducted in the month of June and September, 2010 in Hatkoti, Rohru, Kuthara, Jubbal and Khadapathar areas of major apple producing Shimla district of Himachal Pradesh. A total of 250 samples were collected and analyzed by DAS-ELISA, NASH and RT-PCR. NASH results indicated that a total of 117 samples were infected with Apple chlorotic leaf spot virus (ACLSV), Apple mosaic virus (ApMV), Apple stem grooving virus (ASGV), Apple stem pitting virus (ASPV) and Apple scar skin viroid (ASSVd). Results showed that ASSVd is predominant in these areas with highest infection rate of 27.6% followed by ASPV (17.2%), ACLSV (16.8%), ApMV (15.2%) and ASGV (12%). Mixed infection of these viruses and viroid was frequently detected in apple trees in Himachal Pradesh. The trees, which were positive for viruses and viroids, showed a variety of fruit deformation and rusting symptoms besides leaf deformation, mosaic and chlorosis. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1007/s13337-011-0056-x) contains supplementary material, which is available to authorized users.